Efficacy, Tolerability, and Acceptability of Iron Hydroxide Polymaltose Complex versus Ferrous Sulfate: A Randomized Trial in Pediatric Patients with Iron Deficiency Anemia - Beril Yasa; Leyla Agaoglu; Emin Unuvar (Hindawi Limited, 2011)
Iron polymaltose complex (IPC) offers similar efficacy with superior tolerability to ferrous sulfate in adults, but randomized trials in children are rare. In a prospective, open-label, 4-month study, 103 children aged >6 months with iron deficiency anemia (IDA) were randomized to IPC once daily or ferrous sulfate twice daily, (both 5 mg iron/kg/day). Mean increases in Hb to months 1 and 4 with IPC were 1.2±0.9 g/dL and 2.3±1.3 g/dL, respectively, (both P=0.001 versus baseline) and 1.8±1.7 g/dL and 3.0±2.3 g/dL with ferrous sulfate (both P=0.001 versus baseline) (n.s. between groups). Gastrointestinal adverse events occurred in 26.9% and 50.9% of IPC and ferrous sulfate patients, respectively (P=0.012). Mean acceptability score at month 4 was superior with IPC versus ferrous sulfate (1.63±0.56 versus 2.14±0.75, P=0.001). Efficacy was comparable with IPC and ferrous sulfate over a four-month period in children with IDA, but IPC was associated with fewer gastrointestinal adverse events and better treatment acceptability.